(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article describes the political discourse and its specific features, associated types of analysis. Participants of political discourse and their deliminatin during the communication were also studied. Keywords:political discourse, delimination, conceptual imagery, extralinguistics, politician, communicative phenomena, manipulation, audience, language imagery, semiotic analysis.